2014
DOI: 10.1007/s10877-014-9643-x
|View full text |Cite
|
Sign up to set email alerts
|

Change in auditory evoked potential index and bispectral index during induction of anesthesia with anesthetic drugs

Abstract: The aim of this study was to evaluate the efficacy of the auditory evoked potential (AEP) index (aepEX) as an assessment tool for hypnosis during induction of various anesthetic drugs, and to compare its performance to that of the bispectral index (BIS). A total of 45 cases were divided into three groups based on the drugs used for anesthesia. Before anesthetic induction, BIS and AEP monitors were initiated. Anesthesia was induced through intravenous injection (IV) as follows: MP (n = 15) group, midazolam (0.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…[16] However, ketamine is also a dissociative anesthetic agent that suppresses neuronal function in the cortex and thalamus, and leads to aberrant excitatory activity in the limbic system, including the hippocampus, resulting in electroencephalographic changes distinct from those caused by anesthetics. [17] Ketamine induces a greater increase in the BIS value compared to midazolam in the presence of general anesthesia [18] (ketamine 0.4-0.5 mg/kg increases the BIS value in the presence of propofol or sevoflurane anesthesia [19][20][21] ). Moreover, in our patient, we had to particularly refrain from using muscle relaxants intraoperatively since nerve monitoring was needed to preserve the facial nerve, leading to large dose of intraoperative remifentanil.…”
Section: Discussionmentioning
confidence: 99%
“…[16] However, ketamine is also a dissociative anesthetic agent that suppresses neuronal function in the cortex and thalamus, and leads to aberrant excitatory activity in the limbic system, including the hippocampus, resulting in electroencephalographic changes distinct from those caused by anesthetics. [17] Ketamine induces a greater increase in the BIS value compared to midazolam in the presence of general anesthesia [18] (ketamine 0.4-0.5 mg/kg increases the BIS value in the presence of propofol or sevoflurane anesthesia [19][20][21] ). Moreover, in our patient, we had to particularly refrain from using muscle relaxants intraoperatively since nerve monitoring was needed to preserve the facial nerve, leading to large dose of intraoperative remifentanil.…”
Section: Discussionmentioning
confidence: 99%
“…In a randomized trial in cardiac surgery, these have been shown to reduce the dose requirement for anesthetic agents and the need for intraoperative vasopressors [ 13 ]. Changes in the BAEP index has also been suggested to be more useful than BIS in monitoring the induction of anesthesia, particularly for ketamine [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The MLAEPi is related to the degree of central depression in response to the use of some anesthetics, and it was proposed as a reliable methodology for assessing the depth of the anesthesia [ 23 , 24 , 25 ]. We used the MLAEPi because it is an index which reflects the morphology of the MLAEP curves [ 19 ]. Due to its dynamicity, the morphology of the MLAEPi is difficult to be interpreted during DISE performance.…”
Section: Methodsmentioning
confidence: 99%
“…The current standard used in the clinical setting for monitoring the sedation level is the use of a bispectral index (BIS) [ 18 ], which is based on the detection of spontaneous cortex potentials. Middle latency auditory evoked potentials (MLAEPs) are known as indexes of the central nervous system depression induced by Propofol [ 19 , 20 , 21 ], and an MLAEP index (MLAEPi) is a computed index of potentials of MLAEPs. They are detected in a specific time window of auditory evoked potentials (AEP) on the auditory pathway as a consequence of a definite sound stimulus.…”
Section: Introductionmentioning
confidence: 99%